Baim Wong’s and Atta Halilintar’s Personal Branding through Religious Messages in YouTube Contents - Citra Safira; Hilda Rahmah; Errika Dwi Setya Watie (ETTISAL : Journal of Communication, 2022)
AbstractThis study aims to determine how personal branding forms and the meanings contained in the content shared by Atta Halilintar and Baim Wong using Roland Barthes' Semiotic analysis. The era of disruption provides unlimited space for many people to connect with each other. YouTube is one of the social media that offers a space for relationship and expression, where it is possible for someone to do personal branding in order to show their characteristics and give a different impression from others. Just like Baim Wong and Atta Halilintar, on their personal YouTube channel. Both Atta Halilintar and Baim Wong have a sharing content, both of which show the act of sharing to people who are financially vulnerable. Along with the massive amount of shared content being posted, their actions have been in the spotlight because they were able to touch the religious sentiments of the audience, especially in the midst of a pandemic. Although not a content category for religious creators, both have succeeded in instilling religious messages that tend to increase their popularity and followers on YouTube. Using a qualitative approach, this research involves semiotics as an analytical method to interpret the hidden meaning behind the content by Atta Halilintar and Baim Wong. The results show that religious sentiment is used to emphasize the character of capitalism, because it shows poverty as a commodity.AbstrakPenelitian ini bertujuan untuk mengetahui bagaimana bentuk personal branding dan makna yang terkandung dalam konten berbagi Atta Halilintar dan Baim Wong menggunakan analisis Semiotik Roland Barthes. Era disrupsi memberikan ruang gerak tanpa batas bagi banyak orang untuk terkoneksi satu sama lain. YouTube menjadi salah satu media sosial yang menawarkan ruang untuk berelasi dan berekspresi, dimana hal ini memungkinkan bagi seseorang untuk melakukan personal branding dalam rangka menunjukkan ciri khas dan menampilakan kesan yang berbeda dari orang lain. Begitu pula yang dilakukan oleh Baim Wong dan Atta Halilintar, dalam kanal YouTube pribadinya. Baik Atta Halilintar maupun Baim Wong memiliki muatan konten berbagi, dimana keduanya mempertontonkan aksi berbagi kepada orang-orang yang rentan secara finansial. Seiring masifnya konten berbagi yang diposting, aksi keduanya menjadi sorotan karena mampu menyentuh sisi sentimen religius khalayak, terutama di tengah kondisi pandemi. Meskipun bukan kategori konten kreator religi, kedunya berhasil menanamkan pesan-pesan religius yang bertendensi menaikan popularitas dan pengikutnya di YouTube. Menggunakan pendekatan kualitatif, penelitian ini menggunakan semiotik sebagai metode analisis untuk menafsirkan makna tersembunyi dibalik konten berbagi Atta Halilintar dan Baim Wong. Hasil penelitian menunjukkan bahwa sentimen religius digunakan untuk mempertegas watak kapitalisme, karena mempertontonkan kemiskinan sebagai sebuah komoditas.